Pulmonary Kaposi Sarcoma: An Uncommon Cause of Respiratory Failure in the Era of Highly Active Antiretroviral Therapy—Case Report and Review of the Literature - Stanley M. Nwabudike; Stefan Hemmings; Yonette Paul; Yordanis Habtegebriel; Octavius Polk; Alem Mehari (Case Reports in Infectious Diseases)
Kaposi Sarcoma (KS) is the most common malignancy associated with Acquired Immune Deficiency Syndrome (AIDS) and is caused by Human Herpesvirus 8 (HHV 8) or Kaposi Sarcoma Herpesvirus (KSHV). In about 90% of cases Kaposi Sarcoma is associated with cutaneous lesions; however visceral disease can occur in the absence of cutaneous involvement. In the era of Highly Active Antiretroviral Therapy (HAART), the incidence of KS has declined. Clinical features of pulmonary KS might be difficult to distinguish from pneumonia in the immunocompromised patients and could lead to diagnostic challenges. First-line treatment of KS is with HAART and the incidence has declined with its use. Systemic chemotherapy may play a role depending on the extent of the disease. We report the case of a young man who presented with pulmonary symptoms and was later found to have pulmonary KS. Interestingly this diagnosis was made in the absence of the classic skin lesions. His disease was complicated by progressive respiratory failure and he eventually died.